2‐methoxyestradiol impacts on amino acids‐mediated metabolic reprogramming in osteosarcoma cells by its interaction with NMDA receptor. Issue 11 (6th June 2017) - Gorska‐Ponikowska, Magdalena; Perricone, Ugo; Kuban‐Jankowska, Alicja; Lo Bosco, Giosuè; Barone, Giampaolo
Abstract : Deregulation of serine and glycine metabolism, have been identified to function as metabolic regulators in supporting tumor cell growth. The role of serine and glycine in regulation of cancer cell proliferation is complicated, dependent on concentrations of amino acids and tissue‐specific. D‐serine and glycine are coagonists of N‐methyl‐D‐aspartate (NMDA) receptor subunit GRIN1. Importantly, NMDA receptors are widely expressed in cancer cells and play an important role in regulation of cell death, proliferation, and metabolism of numerous malignancies. The aim of the present work was to associate the metabolism of glycine and D‐serine with the anticancer activity of 2‐methoxyestradiol. 2‐methoxyestradiol is a potent anticancer agent but also a physiological 17β‐ estradiol metabolite. In the study we have chosen two malignant cell lines expressing functional NMDA receptors, that is osteosarcoma 143B and breast cancer MCF7. We used MTS assay, migration assay, flow cytometric analyses, Western blotting and immunoprecipitation techniques as well as molecular modeling studies. We have demonstrated the extensive crosstalk between the deregulated metabolic network and cancer cell signaling. Herein, we observed an anticancer effect of high concentrations of glycine and D‐serine in osteosarcoma cells. In contrast, the amino acids when used at low, physiological concentrations induced the proliferation and migration of osteosarcoma cells. Importantly, the pro‐cancergogenic effects of both glycine and D‐serine where abrogated by the usage of 2‐methoxyestradiol at both physiological and pharmacological relevant concentrations. The obtained data confirmed that 2‐methoxyestradiol may be a physiological anticancer molecule. Abstract : Interaction of 2‐methoxyestradiol with NMDA receptor. GluN1/GluN2A Ligand Binding Domain containing 2‐metoxyestradiol and agonists‐Glycine or D‐Serine.